2019
DOI: 10.1021/acs.jpcc.9b01211
|View full text |Cite
|
Sign up to set email alerts
|

Affordable Estimation of Solvation Contributions to the Adsorption Energies of Oxygenates on Metal Nanoparticles

Abstract: Electrocatalysts are mainly characterized by their intrinsic adsorption properties. However, the observed electrocatalytic activity ultimately results from the interplay between such properties and various additional interactions within the electrified solid-liquid interface. One of such phenomena is solvation, which can substantially affect the stability of adsorbates. The incorporation of solvation in computational electrocatalysis models can be fully implicit (inaccurate for H-bonded adsorbates), fully expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 41 publications
9
73
0
Order By: Relevance
“…where * represents an active site at the NSAs surface. Recent works have shown that three *H 2 O molecules are required to solvate *OH, as the O atom in *OH can make two hydrogen bonds with surrounding water molecules and the H atom can make one . This is also the case for the periodic water bilayers considered here, as shown in Figure a.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…where * represents an active site at the NSAs surface. Recent works have shown that three *H 2 O molecules are required to solvate *OH, as the O atom in *OH can make two hydrogen bonds with surrounding water molecules and the H atom can make one . This is also the case for the periodic water bilayers considered here, as shown in Figure a.…”
Section: Resultssupporting
confidence: 52%
“…Following previous works, to obtain the free energy of solvation (Ω OH ) for *OH on the √3×√3 R30° slab, we determined: (i) the free energy of formation of 1/3 ML *OH coadsorbed with 1/3 ML *H 2 O with respect to an ice‐like water bilayer with 2/3 ML *H 2 O (ΔGOHH2O ), as shown in Equation (1) and in Figure a; and (ii) The free energy of formation of 1/3 ML *OH in vacuum with respect to H 2 O(l) (ΔGOHvac ) using Equation (2), as depicted in Figure b. true2*normalH2normalO*OH+*normalH2normalO+normalH++normale- true*+H2O(l)*OH+normalH++normale- …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…111 Here it is worth mentioning that generalized coordination numbers in conjunction with micro-solvation can also be used to calculate average water stabilization values for extended surfaces and nanoparticles. 112 Additionally, solvation is a crucial factor in studies aimed at breaking scaling relations in solution. As seen in the recent literature, 111 adsorption-energy scaling relations broken under vacuum conditions can, in some cases, be restored in solution by virtue of solvation.…”
Section: Solvent and Electrolyte Effectsmentioning
confidence: 99%